Mathematical Treasure Hunt at UA’s Summer Academy - Paula Oliveira; Andreia Hall; Sónia Pais; Paola Morando; Maria Luisa Sonia Spreafico (Indagatio Didactica, 2025)
Team games offer more than just simple fun. They promote social interaction, communication, cooperation, and healthy competition. These same benefits can be harnessed in educational settings. Gamification strategies have been increasingly adopted in education. In addition to the benefits already mentioned, they also help to increase student engagement and motivation, consolidate knowledge, and improve learning outcomes (Morando and Turconi, 2022; Morando and Spreafico, 2023; Pais and Hall, 2024). This paper presents a mathematics activity carried out during the Summer Academy at the University of Aveiro with 5th and 6th grade students, aged between 10 and 12 years, from diverse places, as well as their perceptions regarding the activity. The activity involved participating in a treasure hunt-style game entitled Basket of Problems, in which teams were challenged to solve a series of problems — in this case, mathematical ones. The solutions to these problems led to the discovery of a magic word. To assess the participants’ perceptions of the activity, a questionnaire was administered. The results indicate that the participants found the activity enjoyable, appreciated working in teams, applied their mathematical knowledge in a playful way, and felt that the activity helped them better understand the importance of mathematics. Furthermore, the results show that the participants would like to carry out activities of this kind in their regular mathematics lessons.